2020
DOI: 10.1111/cpr.12879
|View full text |Cite
|
Sign up to set email alerts
|

LncRNAs are regulated by chromatin states and affect the skeletal muscle cell differentiation

Abstract: Objective This study aims to clarify the mechanisms underlying transcriptional regulation and regulatory roles of lncRNAs in skeletal muscle cell differentiation. Methods We analysed the expression patterns of lncRNAs via time‐course RNA‐seq. Then, we further combined the ATAC‐seq and ChIP‐seq to investigate the governing mechanisms of transcriptional regulation of differentially expressed (DE) lncRNAs. Weighted correlation network analysis and GO analysis were conducted to identify the transcription factor (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…Some lncRNAs play functional roles in myoblast proliferation and differentiation, such as lnc-ORA [ 49 ], IGF2 AS [ 50 ], SMUL [ 51 ], and lncIRS1 [ 52 ]. In this study, we found that the expression of Gm10561 was upregulated during C2C12 differentiation, consistent with a previous report [ 41 ]. Knockdown of Gm10561 remarkably suppressed proliferation and differentiation of C2C12 myoblasts, while Gm10561 overexpression had the opposite effect.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Some lncRNAs play functional roles in myoblast proliferation and differentiation, such as lnc-ORA [ 49 ], IGF2 AS [ 50 ], SMUL [ 51 ], and lncIRS1 [ 52 ]. In this study, we found that the expression of Gm10561 was upregulated during C2C12 differentiation, consistent with a previous report [ 41 ]. Knockdown of Gm10561 remarkably suppressed proliferation and differentiation of C2C12 myoblasts, while Gm10561 overexpression had the opposite effect.…”
Section: Discussionsupporting
confidence: 93%
“…A recent study identified 385 differential expressed lncRNAs during C2C12 differentiation, whose expression were controlled by changes of chromatin state, using RNA-seq combined with ATAC-seq and ChIP-seq analysis. G m10561 was one of the differentially expressed lncRNAs [ 41 ]. However, the role of Gm10561 in myogenesis is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the foetal stage is the critical period of myogenesis, when the majority of skeletal muscle fibres form 5 . It has become established that many specific signalling pathways and transcription factors (TFs) are involved in myogenesis 5–8 . Wingless and Int (Wnt), paired box 3 ( Pax3 ), and Pax7 are necessary myogenic regulatory factors ( MRFs ) that regulate the myogenic lineage differentiation of mesenchymal stem cells during embryo stage 5,9–12 .…”
Section: Introductionmentioning
confidence: 99%
“…5 It has become established that many specific signalling pathways and transcription factors (TFs) are involved in myogenesis. [5][6][7][8] Wingless and Int (Wnt), paired box 3 (Pax3), and Pax7 are necessary myogenic regulatory factors (MRFs) that regulate the myogenic lineage differentiation of mesenchymal stem cells during embryo stage. 5,[9][10][11][12] Although previous studies provide strong evidence of the contribution by MRFs to skeletal muscle development, 13,14 the precise mechanisms underlying skeletal muscle development remain unclear.…”
mentioning
confidence: 99%
“…Current evidence suggests that lncRNAs may act as molecular sponges of miRNAs via their miRNA response elements (MREs) for the regulation of miRNA expression, thereby depressing the speci c target genes of the miRNAs, which is described as the competing endogenous RNA (ceRNA) hypothesis. lncRNAs have been demonstrated to play crucial roles in various biological processes, such as in ammation, proliferation, differentiation, immune escape, migration and apoptosis [27][28][29][30][31]. Accumulating evidence suggests that this regulatory action plays pivotal roles during the development of ischemic stroke [32][33][34].…”
Section: Introductionmentioning
confidence: 99%